2005
DOI: 10.1128/aem.71.12.8008-8015.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of Escherichia coli O157:H7 to Alfalfa, Human Epithelial Cells, and Plastic Is Mediated by a Variety of Surface Structures

Abstract: Escherichia coli O157:H7 carried on plant surfaces, including alfalfa sprouts, has been implicated in food poisoning and outbreaks of disease in the United States. Adhesion to cell surfaces is a key component for bacterial establishment and colonization on many types of surfaces. Several E. coli O157:H7 surface proteins are thought to be important for adhesion and/or biofilm formation. Therefore, we examined whether mutations in several genes encoding potential adhesins and regulators of adherence have an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 51 publications
(60 reference statements)
3
99
0
Order By: Relevance
“…These studies uncovered several new genes that are involved in biofilm formation. Our approach was not complete, however, as we also missed some genes already shown to be involved in biofilm formation in E. coli O157:H7, such as csgD, ompA, and cadA (58). This is because our screen was not saturating.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These studies uncovered several new genes that are involved in biofilm formation. Our approach was not complete, however, as we also missed some genes already shown to be involved in biofilm formation in E. coli O157:H7, such as csgD, ompA, and cadA (58). This is because our screen was not saturating.…”
Section: Discussionmentioning
confidence: 87%
“…Because of this complexity, the process of biofilm formation and its regulation is poorly understood. Previous studies in E. coli O157:H7 have focused on individual genes and the specific genetic pathways that are responsible for biofilm formation (10,51,58,60). In contrast, few studies have focused on studying genetic factors that control E. coli O157:H7 biofilm formation on a global scale, although studies of this type have been performed with other bacterial pathogens (43,47,59).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Enterohemorrhagic E. coli of serotype O157:H7 utilizes OmpA in adhering to HeLa epithelial cells and Caco-2 colonic epithelial cells (46). OmpA also appears to be critical in adherence to plant surfaces, as an ompA mutant of E. coli O157 did not colonize alfalfa bean sprouts (47). In addition, OmpA, together with the Hek protein, has been shown to be critical for the invasion of colonic epithelial cells by meningitic E. coli (48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no changes in the ability of prototype EHEC strain 86-24, compared to that of the double mutant strain, to adhere to Caco-2 cells, alfalfa sprouts, and seed coats were observed (89). These studies indicated that Cah plays a role in bacterial autoaggregation, but not in adherence of STEC to cells.…”
Section: Stec Autotransportersmentioning
confidence: 69%